Speeding up systems biology simulations of biochemical pathways using condor. (5th December 2013) - Liu, Xuan; Taylor, Simon J. E.; Mustafee, Navonil; Wang, Jun; Gao, Qian; Gilbert, David
SUMMARY Systems biology is a scientific field that uses computational modelling to study biological and biochemical systems. The simulation and analysis of models of these systems typically explore behaviour over a wide range of parameter values; as such, they are usually characterised by the need for nontrivial amounts of computing power. Grid computing provides access to such computational resources. In previous research, we created the grid‐enabled biochemical networks simulation environment to attempt to speed up system biology simulations over a grid (the UK National Grid Service and ScotGrid). Following on from this work, we have created the simulation modelling of the epidermal growth factor receptor microtubule‐associated proteinkinase pathway utility, a standalone simulation tool dedicated to the modelling and analysis of the epidermal growth factor receptor microtubule‐associated protein kinase pathway. This builds on experiences from biochemical networks simulation environment by decoupling the simulation modelling elements from the Grid middleware. This new utility enables us to interface with different grid technologies. This paper therefore describes the new SIMAP utility and an empirical investigation of its performance when deployed over a desktop grid based on the high throughput computing middleware Condor. We present our results based on a case study with a model of the mammalian ErbB signalling pathway, a pathway strongly linked to cancer. Copyright © 2013 John Wiley & Sons, Ltd.